It’s Time For Long-Term Care Home To Make Mental Health A Priority - Chee, Kwan Foong* (Reach Publishing Sdn Bhd, 2024)
The 2024 World Mental Health Day theme, “It’s Time to Prioritize Mental Health in the Workplace,” highlights the need to focus on mental well-being in long-term care facilities, often a new ‘workplace’ for many elders. The challenge is to shift from prioritising physical care to recognising mental health as equally essential for overall well-being.